2015
DOI: 10.1039/c5dt02276b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and post-synthetic modification of amine-, alkyne-, azide- and nitro-functionalized metal–organic frameworks based on DUT-5

Abstract: Functionalized 4,4'-biphenyldicarboxylic acid molecules with additional amine, alkyne, azide or nitro groups were prepared and applied in the synthesis of novel metal-organic frameworks and mixed-linker metal-organic frameworks isoreticular to DUT-5. The properties of the frameworks could be tuned by varying the number of functional groups in the materials and the amine groups were employed in post-synthetic modification reactions without changing the framework structure or significantly decreasing the porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 59 publications
1
34
1
Order By: Relevance
“…To design MOFs with desired properties, the introduction of various functional groups into MOFs has attracted considerable interests. Postsynthetic covalent modication provides a variety of means to chemically modify the structures of MOFs, [18][19][20][21] among which the direct graing of functional groups on the organic linkers is effective, and has been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…To design MOFs with desired properties, the introduction of various functional groups into MOFs has attracted considerable interests. Postsynthetic covalent modication provides a variety of means to chemically modify the structures of MOFs, [18][19][20][21] among which the direct graing of functional groups on the organic linkers is effective, and has been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative proof for the incorporation of multiple linkers is usually unproblematic and can be confirmed by IR spectroscopy, XPS, XAS, solid‐state NMR spectroscopy and in some cases by single‐crystal analysis ( D ) . Moreover, UV/Vis spectroscopy can be used to prove the incorporation of certain linkers and might be able to quantify the linker ratios for certain systems …”
Section: Mixed‐linker Metal–organic Frameworkmentioning
confidence: 99%
“…[66] Copyright 2014, American Chemical Society. [64] Recently, it was demonstrated that monolithic MOF multilayers can be grown on a surface in a controlled way, using a step-by-step sequential procedure called liquid-phase epitaxy (LPE). Adapted with permission.…”
Section: Research Activities In Smlmentioning
confidence: 99%